EVALUATION OF EFFECTIVENESS OF COMMUNITY EMPOWERMENT PROGRAMS IN ALLEVIATING EKSTREME POVERTY IN BANGIO VILLAGE - Maryam S. Limbotu; Aryati Hamzah; Nur Rizky Putri Mahadi (LP2M Universitas Bina Mandiri Gorontalo, 2025)
This study aims to determine the extent to which community empowerment programs increase the income of low-income families in Bangio Village and to identify the challenges encountered in implementing these programs. This research method uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation with informants in this study, including the Village Head, BUMDes Director, BUMDes Secretary, and the community. The research results show that 1. community empowerment programs have great potential to significantly increase the incomes of low-income families, mainly when supported by strong integration among various social and economic interventions and by continuous government and local community support. This integration includes cross-sector collaboration to ensure that social assistance, skills training, and access to financial and social services are synchronized and appropriately targeted to the needs of the village community. 2. The main challenges in implementing community empowerment programs in Bangio village include several key aspects—first, the limitation of human resources. Many residents still rely on external parties due to a lack of skills in project management and technology use, which risks the program not operating optimally and becoming unsustainable.